Levinas and the photographic undergone. (1st December 2015) - Hunting, John
A Levinasian approach to the photographic offers a unique opportunity to reconsider Levinas' claim that the 'face' cannot be seen. Levinas' reading of Husserl on time consciousness in mind, it is argued that vision marries an incommensurable debt and reply, a duplicitous interface that is the very expression of embodiment and condition of the face. Brand's and Pinchevski's approach to the face and to photography, as incompatible yet necessary conjunctions of address and image, is recruited to advance the thesis that the duplicity belonging to vision and to the face is made explicit when looking at photographs and films. The duplicity of the 'photographic undergone', both compelling vision and engineering the self-same, explains as much. Of course the photographic may or may not attest to the face – as address and image, interruption and response, debt and reply – but even when it does the attestation is never without ambiguity and trouble, violations and doubt.